When the Sad Past Is Left: The Mental Metaphors Between Time, Valence, and Space - Spatola, Nicolas; Santiago, Julio; Beffara, Brice; Mermillod, Martial; Ferrand, Ludovic; Ouellet, Marc (Frontiers in Psychology, 2018)
A mental metaphor is a strategy that consists of completing the representation of a concept with structural components of a correlating concept. Three issues were addressed here to deepen our understanding of this mechanism: the use of mental metaphors between abstract concepts, the simultaneous activation of multiple mental metaphors and the importance of the focus of attention on the relevant dimensions of a mental metaphor. In two experiments, participants made temporal or valence judgments (with their left or right hand) on verbs with a negative or positive meaning and conjugated in the past or future form, allowing for the simultaneous activation of the “time is space”, “valence is space” and “time is valence” mental metaphors. Left-past/right-future and left-negative/right-positive congruency effects were found, and these effects were greater in the temporal and valence judgment tasks, respectively, demonstrating the importance of attentional cuing. Simultaneously, a congruency effect between the abstract concepts of time and valence (past-negative/future-positive) was observed, revealing that a mental metaphor can occur between abstract concepts and that multiple metaphors can be processed simultaneously. These results are discussed in terms of different theories within the field of mental metaphors.